Mutation Status and Immunoglobulin Gene Rearrangements in Patients from Northwest and Central Region of Spain with Chronic Lymphocytic Leukemia. (30th March 2014) - González-Gascón y Marín, I.; Hernández, J. A.; Martín, A.; Alcoceba, M.; Sarasquete, M. E.; Rodríguez-Vicente, A.; Heras, C.; de las Heras, N.; Fisac, R.; García de Coca, A.; de la Fuente, I.; Hernández-Sánchez, M.; et al.
Abstract : The aim of this study was to investigate the frequency and mutation status of the immunoglobulin heavy variable chain (IGHV) in a cohort of 224 patients from northwest and central region of Spain diagnosed with chronic lymphocytic leukemia (CLL), and to correlate it with cytogenetic abnormalities, overall survival (OS) and time to first treatment (TTFT). 125 patients had mutated IGHV, while 99 had unmutated IGHV. The most frequently used IGHV family was IGHV3, followed by IGHV1 and IGHV4. The regions IGHV3-30, IGHV1-69, IGHV3-23, and IGHV4-34 were the most commonly used. Only 3.1% of the patients belonged to the subfamily IGHV3-21 and we failed to demonstrate a worse clinical outcome in this subgroup. The IGHV4 family appeared more frequently with mutated pattern, similar to IGHV3-23 and IGHV3-74. By contrast, IGHV1-69 was expressed at a higher frequency in unmutated CLL patients. All the cases from IGHV3-11 and almost all from IGHV5-51 subfamily belonged to the group of unmutated CLL.